2019
DOI: 10.1186/s12936-019-2795-x
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, seasonal abundance and distribution of potential anopheline vectors in a malaria endemic area of Iran: field assessment for malaria elimination

Abstract: Background Despite decreases in incidence, malaria remains a major public health challenge in south and southeast Iran, where vector control is considered one of the main strategies for elimination of the disease. The efficacy of this strategy depends on understanding malaria vector ecology, which varies by species. This study was conducted to determine the species composition, seasonal abundance and distribution of potential anopheline vectors in Bashagard County, one of the important malaria-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Similarly, data are presented by the topography of collection sites in few studies that paid attention to the vertical distribution of mosquito larval habitats. 27,64 In these investigations, there is no reference level to understand what they mean by mountainous or foothill areas.…”
Section: Anopheles Clavigermentioning
confidence: 99%
“…Similarly, data are presented by the topography of collection sites in few studies that paid attention to the vertical distribution of mosquito larval habitats. 27,64 In these investigations, there is no reference level to understand what they mean by mountainous or foothill areas.…”
Section: Anopheles Clavigermentioning
confidence: 99%
“…We propose that other investigations on the prediction ability of vector species for malaria risk be conducted in the future according to the quality of LLN used. Although major vector species are not the same in Africa and in Asia, a study by Soleimani-Ahmadi, conducted in Iran, found a substantial difference in the reduction of malaria risk between the use of non-treated nets and Olyset nets (Soleimani-Ahmadi et al 2012;Sanei-Dehkordi et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to combine vector factors, environmental characteristics and socio-economic factors to investigate malaria risk. According to a study by Sanei-Dehkordi et al (2019), combining several strategies according to malaria vector characteristics is the most effective way to fight malaria. The study of environmental characteristics and malaria vectors is important in strategic axes of humanvector interaction control which could lead to a reduction in malaria prevalence (Pages et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The rise of malaria cases in these months may be because of high vector density and increase in the biting rates of malaria vectors. The seasonal abundance pattern of these vectors in different habitats was signi cantly higher in monsoon season than that of pre-and post-monsoon season (Mohapatra et al, 2003;Sanei-Dehkordi et al, 2019). Higher number of malaria cases in this region may be because of the presence of many breeding habitats throughout the year with favorable temperature that led to constant risk of malaria transmission (Shil and Balasubramanian, 2020).…”
Section: Discussionmentioning
confidence: 99%